Evil, Agency, and Citizenship Education - den Heyer, Kent; van Kessel, Cathryn (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2015)
We all have a sense of evil, but many of us do not ponder its nature or the ways in which our beliefs about evil shape what we teach and learn about the actions of citizens in historical or contemporary times. We argue that the word and concept of evil can be detrimental to the development of good citizens when it is used as a political and educational shibboleth to shut down critical thought about traumatic historical and contemporary events. Read through the work of Hannah Arendt and Alain Badiou, however, a pedagogical engagement with our understandings of evil offers an opportunity to learn from difficult events in a way that might inform contemporary action towards a less violent future.